Assessment of Public Awareness of Climate Change in Logar Province - Shirzad, Mohammad Dawod; Sahak, Kawoon; Farhat, Ehsanullah (Journal of Natural Sciences – Kabul University, 2026)
Climate change is a significant environmental challenge caused by human activities, particularly the increasing use of fossil fuels, which negatively impacts the environment, water resources, and the intensity of natural hazards such as floods and droughts. This study aimed to assess public awareness of climate change in Logar Province. A quantitative approach was employed, and 384 participants were selected through random sampling. Data were collected using a structured questionnaire and analyzed with statistical methods. The findings indicate that the overall awareness of climate change among the population is 68%, the perception of its impacts is 66%, access to information sources is 34%, and engagement in climate-related actions is 45%. These results suggest that although general awareness is moderate, limited access to information and low participation in adaptive measures reduce the community’s capacity to respond effectively to climate change.